Fatal hyperprogression induced by nivolumab in metastatic renal cell carcinoma with sarcomatoid features: a case report. Issue 2 (27th August 2020) - Dionese, Michele; Pierantoni, Francesco; Maruzzo, Marco; Bimbatti, Davide; Deppieri, Filippo M.; Maran, Michela; Gardiman, Marina P.; Basso, Umberto
Abstract : In the past few years, the immune checkpoint inhibitor (ICI) nivolumab has become standard of care in the treatment of metastatic renal cell carcinoma (mRCC) progressing after antiangiogenic agents. To date, neither expression of programmed death ligand-1 (PD-L1) nor any other biomarker can be used to predict responses to ICIs, although intermediate–poor International Metastatic Database of Renal Carcinoma (IMDC) risk patients and those with sarcomatoid tumors appear to achieve superior benefit from immunotherapy. Paradoxically, ICIs may sometimes increase the speed of tumor growth. This rare phenomenon, called hyperprogression, has first been described in patients with melanoma and lung cancer treated with ICIs and is associated with poor survival. Here, we present the case of a patient affected by an intermediate IMDC risk mRCC with diffuse sarcomatoid features who achieved long disease control with first-line sunitinib and then started a second-line treatment with nivolumab. Unexpectedly, he experienced a dramatic acceleration of tumor growth and died soon after the third infusion of nivolumab. Then, we review the frequency of hyperprogression in mRCC and discuss the biological peculiarity of sarcomatoid RCC in terms of different responses to ICIs and antiangiogenic agents.